2019
DOI: 10.25135/rnp.150.19.07.1321
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antibacterial, Antioxidant and Cytotoxic Activities of the Essential Oil of Dianella ensifolia

Abstract: The essential oil (EO) was isolated from aerial parts of Dianella ensifolia (L.) DC by hydro-distillation and its chemical constituents was determined by GC-FID and GC-MS. In total, sixty-three compounds comprising 97.2% of the EO were identified. The major compounds in D. ensifolia EO were found to be allo-aromadendrene (7.3%), geranylacetone (6.2%), hexahydrofarnesyl acetone (4.4%), longifolene (4.2%) and β-caryophyllene (4.0%). Besides, the essential oil was evaluated for its antibacterial activity by disc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Additionally, ionone compounds have been described as having a repellent effect against the spider mite Tetranychus urticae [ 72 ], one of the most important pathologies in the Asparagus genus. Aromatic monoterpenes, such as geranyl derivatives (about 20% of the total scent), were emitted by A. acutifolius and are found in many plants’ essential oils [ 73 , 74 ]. Geranyl acetone has been shown to play an important role in plant–pollinator interactions, to have antibacterial effects against many bacterial strains, and to exhibit antioxidant activity [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, ionone compounds have been described as having a repellent effect against the spider mite Tetranychus urticae [ 72 ], one of the most important pathologies in the Asparagus genus. Aromatic monoterpenes, such as geranyl derivatives (about 20% of the total scent), were emitted by A. acutifolius and are found in many plants’ essential oils [ 73 , 74 ]. Geranyl acetone has been shown to play an important role in plant–pollinator interactions, to have antibacterial effects against many bacterial strains, and to exhibit antioxidant activity [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aromatic monoterpenes, such as geranyl derivatives (about 20% of the total scent), were emitted by A. acutifolius and are found in many plants’ essential oils [ 73 , 74 ]. Geranyl acetone has been shown to play an important role in plant–pollinator interactions, to have antibacterial effects against many bacterial strains, and to exhibit antioxidant activity [ 74 ]. Thus, the volatile profiles of the two species, especially that of A. albus , conformed to the attraction–information function appropriate to the sensitivity of their main pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…This monoterpene was shown as a major constituent of the volatile compound mixture, present at a concentration of about 283 μg/mL in the distilled sample [ 30 ]. An independent study identified geranylacetone as a major component of Dianella ensifolia (6% GC-MS) [ 31 ]. This study conducted a series of in vitro experiments to understand the antioxidant potential of this oil.…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
“…The studies indicate that this compound might hit several targets as these biological processes involve different pathways. The pharmacological effects of lavender oil depend on the concentration of lavandulyl acetate as independent studies have also shown other biological activities for this essential oil [ 31 ].…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
“…Essential oils from the aerial parts exhibited broad-spectrum in vitro antibacterial activity against both Gram-positive and Gram-negative bacteria also the in vitro cytotoxic activity evaluation against the cell lines of HepG2 (liver hepatocellular cells) and MCF-7 (human breast adenocarcinoma cell line) by MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay method. The screening showed potent cytotoxicity of cells in the IC 50 values of 61.35 and 56.53 μg/mL respectively (He et al 2019). From the air-dried roots, a new cycloartane-type triterpenoid 22-hydroxy-cyclolaudenol was isolated together with two known triterpenoids cycloneolitsol and cyclopholidonol showing significant cytotoxic effects against cancer cells (Tang et al 2016).…”
Section: Phytochemistrymentioning
confidence: 99%